WOMEN'S DIVORCE CASES IN THE 17TH CENTURY IN ISTANBUL QADI REGISTERS - Nuredini, Melek (International Scientific Journal Vision, 2020)
Through registers we can see important information about family law from the Ottoman period. According to what we have learned from the data obtained, the amount of mahr (reward) given to women from the marriage contract is frequently seen in the sharia registers in case of divorce. Alimony is a woman's pursuit of her legal rights and the protection of these rights by the court in various matters. Economic structure was basically determined by the principles of Islamic law. In many areas of Ottoman and Middle Eastern studies, registers have been used extensively as primary historical sources. Women's studies, Muslim and non-Muslim relations, material culture of society, Ottoman law studies and other subjects have witnessed new readings and understandings through the use of registers. We see that subject such as the city, economy, family, law, biography of women, army, foundations, population, disease, slaves are emphasized. In this study, we focused mostly on the divorce of men and women, the emancipation of concubines, and the position of women and children in the society in social, cultural, legal and economic issues in the Ottoman society in the 17th century Istanbul registers.